Application of The Properties of Naqli And Aqli in Positive Law with Respect to Islamic Contract Law - Irena Dwi Fetraningtyas; Yunanto Yunanto (Syariah: Jurnal Hukum dan Pemikiran, 2021)
Abstrak: Konsep bertransaksi dalam Ekonomi Islam disebut sebagai akad. Akad adalah perikatan yang ditetapkan dengan ijab dan qabul berdasarkan ketentuan syara’ yang berdampak pada objeknya. Semua perikatan atau transaksi yang dilakukan oleh para pihak, dua pihak atau lebih tidak boleh menyimpang dan sejalan dengan kehendak sya’riat. Tidak boleh ada kesepakatan untuk menipu orang lain, tidak boleh bertransaksi yang mengandung unsur maisir, gharar, riba dan bathil. Serta tidak boleh bertransaksi dengan barang atau harta yang diharamkan, maal ghairu mutaqawwim. Dalam bertransaksi secara ekonomi Islam, terdapat dalil Naqli dan Aqli. Dalil naqli dapat diartikan sebagai tanda bukti atau petunjuk dari teks ayat Al-Quran, dalil tersebut kebenarannya merupakan mutlak atau hakiki. Sedangkan yang dimaksud dengan dalil Aqli adalah dalil yang dapat dinalar oleh akal fikiran. Dua dalil tersebut lahirlah dasar atau prinsip ekonomi Islam yang tidak boleh menyimpang dari Al-Quran dan Al-Hadits. Hal tersebutlah yang akan melahirkan asas-asas kebolehan dalam ekonomi Islam. Penelitian ini akan membahas bagaimana fungsi dalil Naqli dan Aqli dalam Hukum Ekonomi Islam, dan bagaimana penerapan Dalil Naqli dan Aqli dalam Hukum Positif Berkenaan Dengan Hukum Akad (Perjanjian) Islam. Kata Kunci: Akad, Ekonomi Islam, Dalil Naqli dan Aqli. Abstract: the concept of dealing in Islamic economics is called contract. An contract is an agreement that is determined by consent and qabul based on the provisions of syara’ have an impact on the object. All agreement or transactions made by the parties, two or more parties may not deviate and in accordance with the wishes of the faith. There must be no agreement to deceive others, no transactions containing elements of maisir, gharar, usury and bathil. And may not deal with goods or property that is forbidden, called as Maal ghairu mutaqawwim. In transacting economically in Islam, there is the proposition of Naqli and Aqli. Naqli theorem can be interpreted as evidence or indications from the text of the verses of the Quran, the argument is the truth is absolute or haqiqi. The argument of the Aqli is the proposition that can be reasoned by logic. These two propositions were born as the basic principles of Islamic economics that must not deviate from the Al-Quran and Al-Hadith. This research will discuss how the function Naqli and Aqli arguments are in Islamic Economic Law, and how the application of Naqli and Aqli propositions in Positive Law with regard to Islamic contract Law.Key Words: Contract, Economic Islam, Propositions of Naqli and Aqli.